Sexual Dimorphism Impact on the Ground Reaction Force Acting on the Mediolateral Direction During Level Walking: Hip Abductor Muscle Biomechanics and Its Correlation to GRF Moment Arm - Abd-Eltawab, Amany E.; Ameer, Mariam A.; Eladl, Mohamed Ahmed; El-Sherbiny, Mohamed; Ebrahim, Hasnaa Ali; Elsherbini, Dalia Mahmoud Abdelmonem (Frontiers in Bioengineering and Biotechnology, 2022)
The female pelvis morphology represents an evolved compensation between two opposing needs: a broad pelvis enough to deliver a sizeable brained offspring while remaining narrow enough to allow for effective bipedal gait. The precise expectation of hip abductor force generation is critical in anthropological studies and experimental practice of human stride mechanics. Hip implants and surgical procedures for hip anatomy reconstruction are based on the static single-leg stance paradigm. The current work investigated the impact of sexual dimorphism on the ground reaction force (GRF) acting on the mediolateral direction during level walking, emphasizing the difference in hip abductor muscle biomechanics and its correlation to ground reaction force moment arm, R. The ground reaction force in the mediolateral direction, hip abduction and adduction moments during the gait cycle and ground reaction force moment arm, R were measured. The current study concludes that the male individuals exhibit significantly higher mass-specific mediolateral ground reaction force during level walking. In contrast, hip abductor moments/kg body weight, medialization of the trochanter, R, and hip coronal were more significant in female individuals. We conclude that increased abductor moment and medialization of the greater trochanter will increase R, hip coronal and decrease abductor moment arm, r, in female individuals, affecting the effective mechanical advantage (EMA) of hip abductors in single-limb stance during level walking.